Pengaruh Terapi Storytelling Menggunakan Boneka Tangan Terhadap Tingkat Kecemasan Anak Selama Hospitalisasi Di Ruang Pandawa RSU Diponegoro Dua Satu Klaten - Putri Sulistyowati; Sutrisno Sutrisno; Widiyono Widiyono (JOURNAL SAINS STUDENT RESEARCH, 2026)
Hospitalization is an experience that can trigger anxiety in children due to an unfamiliar environment, medical procedures, and separation from family. One non-pharmacological intervention that can be used to reduce anxiety is storytelling therapy using hand puppets. To determine the effect of storytelling therapy using hand puppets on children's anxiety levels during hospitalization in the Pandawa Ward at Diponegoro Dua Satu Klaten General Hospital. This study employed a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 30 respondents, comprising 15 children in the intervention group and 15 children in the control group. Anxiety levels were measured before and after the intervention. Data analysis involved a paired t-test for pretest and posttest scores within both the intervention and control groups, and an independent t-test to compare the effects between the intervention and control groups' posttest scores. The results showed a significant decrease in anxiety levels in both the intervention and control groups (p<0.001). The independent t-test results indicated a significant difference in anxiety levels between the two groups following the intervention (p=0.009); thus, storytelling therapy using hand puppets proved more effective in reducing children's anxiety levels during hospitalization compared to other play therapies. Storytelling therapy using hand puppets influences the reduction of children's anxiety levels during hospitalization and is more effective than other play therapies. This intervention can be utilized as a form of atraumatic play therapy in pediatric nursing care.